Food recipe related social platform - Ang, Yik Hang (2021)
In order to achieve long-distance communication, social platform has played a very important role in this modern era because it can connect people all over the world. For ordinary social networks like Instagram and Facebook, the information published on these channels usually has a high diversity. If the social network doesn’t have a specific theme like food, it may cause problem for users that want to look for particular relevant content such as food recipes. In social network like Facebook, users face difficulty when searching for a recipe that only serves one people and have a less than twenty minutes cook time because Facebook is not specific for recipes sharing. Besides that, ordinary social network has made it more difficult for user to make friends that have same interest as well. Therefore, food social network is necessary to be proposed to solve such problem. The final deliverable of this project is a food-recipes social platform that can gather users with the same interest and share food-related information and recipes. By using the template provided in this food recipe social network, users can categorize the recipe, state the serve size and cook time before publishing to the community. Besides that, this social network also allow user to publish posts to reflect the food taste, service quality and sanitary condition of visited restaurant so other user can get basic understanding of that restaurant before visit there. Several food social networks have been reviewed in order to study the working logic of similar social network. Basic functionalities such as sign up, login, register and logout are implemented as well to make the application more systematic. This project is developed as an android native application using java and firebase as a backend for authentication and storing all data. Moreover, agile method is implemented during development which is prototype approach, the continuous improvements are implemented based on the initial project prototype until delivered a final product. The agile development approach can reduce cost and time required to develop a mobile application project. Although this project is completed, but improvements can still be done in the future.